Outflows, envelopes, and disks as evolutionary indicators in Lupus YSOs - Vazzano, María Mercedes (2021)
Context. The Lupus star-forming complex includes some of the closest low-mass star-forming regions, and together they house objects that span evolutionary stages from prestellar to premain sequence. Aims. By studying seven objects in the Lupus clouds from prestellar to protostellar stages, we aim to test if a coherence exists between commonly used evolutionary tracers. Methods. We present Atacama Large Millimeter Array (ALMA) observations of the 1.3mm continuum and molecular line emission that probe the dense gas and dust of cores (continuum, C18O, N2D+) and their associated molecular outflows (12CO). Our selection of sources in a common environment, with an identical observing strategy, allows for a consistent comparison across different evolutionary stages. We complement our study with continuum and line emission from the ALMA archive in different bands. Results. The quality of the ALMA molecular data allows us to reveal the nature of the molecular outflows in the sample by studying their morphology and kinematics, through interferometric mosaics covering their full extent. The interferometric images in IRAS 15398-3359 appear to show that it drives a precessing episodic jet-driven outflow with at least four ejections separated by periods of time between 50 and 80 yr, while data in IRAS 16059-3857 show similarities with a wide-angle wind model also showing signs of being episodic. The outflow of J160115-41523 could be better explained with the wide-angle wind model as well, but new observations are needed to further explore its nature. We find that the most common evolutionary tracers in the literature are useful for broad evolutionary classifications, but they are not consistent with each other to provide enough granularity to disentangle a different evolutionary stage of sources that belong to the same Class (0, I, II, or III). The evolutionary classification revealed by our analysis coincides with those determined by previous studies for all of our sources except J160115-41523. Outflow properties used as protostellar age tracers, such as mass, momentum, energy, and opening angle, may suffer from differences in the nature of each outflow and, therefore, detailed observations are needed to refine evolutionary classifications. We found both AzTEC-lup1-2 and AzTEC-lup3-5 to be in the prestellar stage, with the possibility that the latter is a more evolved source. IRAS 15398-3359, IRAS 16059-3857, and J160115-41523, which have clearly detected outflows, are Class 0 sources, although, we are not able to determine which is younger and which is older. Finally Sz 102 and Merin 28 are the most evolved sources in our sample and show signs of having associated outflows, which are not as well traced by CO as for the younger sources.